Upaya Meningkatkan Kecerdasan Visual Spasial Melalui Permainan Puzzle Pada Anak Kelompok A Di TK Aisyiyah Pabelan Kartasura Sukoharjo Tahun Ajaran 2016/2017 - Hakim, Assabila; , Dr. Darsinah, M.Si (2017)
The aim of this study is to enhance the spacial visual intelligence using puzzle game to group A students of Aisyiyah Kindergarten Pabelan Kartasura Sukoharjo in the academic year of 2016/2017. This study uses Classroom Action Research (CAR) which is conducted in two stages, including cycle I and cycle II. The subjects of this study are 13 students. The data collection uses naturalistic observation and documentation. The students data analysis is comparative and one-way anova analysis. The teacher data analysis is interactive analysis. The percentage of the pre cycle reaches 48%. After the cyclical action I, the result reaches 65.2%, and reaches 87.7% in the cyclical action II. The result of one-way anova is F-hitung 36.051 and F-tabel 5.18 using the level of confidence of 99%. Thus, F-hitung > F-tabel, which means Ha is accepted. It can be concluded that puzzle game can enhance spacial visual intelligence of group A students of Aisyiyah Kindergarten Pabelan Kartasura Sukoharjo in the academic year of 2016/2017. Keywords: Puzzle game, Spacial Visual Intelligence